Analisis Penerapan Sistem Informasi Akuntansi Penjualan pada PT. Mitra Patriajaya Abadi - Vicky Verantika (PUTRA JAWA PUBLISHER, 2023)
Accounting information plays an important role in decision-making, especially in today's highly competitive business environment where a good information system is essential to remain competitive. One of the key factors in maintaining competitiveness is productivity. By implementing a good accounting information system, companies can improve their sales transaction processes. This article aims to explore how the sales accounting information system has been applied at PT. Mitra Patriajaya Abadi. The research method used is a descriptive one, employing field research that involves interviews, observations, and documentation. The study found that the sales systems and procedures implemented by the management of PT. Mitra Patriajaya Abadi are effective and adequate, meeting various assessment criteria that show they have been implemented effectively.